PENGEMBANGAN MODUL PEMBELAJARAN TRIGONOMETRI BERBASIS SOAL PEMECAHAN MASALAH UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Hafizatunnisa, Hafizatunnisa (Departemen Matematika, 2023)
Teaching materials type used in school is learning modules. The modules are still general in nature and not optimal for familiarizing students with problem solving questions. Therefore, develop learning modules based on problem-solving so that students are familiar with problem-solving questions. The research objective is to produce products that criteria are valid, practical, and effective. The results obtained a very valid and very practical problem solving-based trigonometry learning module with a score of 88.88 and 90.19. The level of effectiveness is high with an N-gain value of 0.77. Based on these data concluded the trigonometry learning modules based on problem-solving that has been developed is criteria as very valid, very practical, and high effective to improve mathematical problem-solving abilities.Keywords– Module, Trigonometry, Valid, Practical, Effective